A Cousin's Prayer - Brunstetter, Wanda E. (Uhrichsville, Ohio : Barbour Publishing, 2013)
Traumatized after surviving an automobile accident in which her boyfriend was killed, Katie Miller struggles to find her way out of depression, while Freeman Bontrager tries to gain Katie's trust in hopes of winning her heart.
Keywords: Amish -- Fiction; Indiana -- Fiction; Christian fiction; Love stories